Occurance of Ectoparasite-Small Mammals in Hutan Lagenda and Waterfall of Gunung Ledang - H'ng, Yan Ting; Sapaat, Arney (Enhanced Knowledge in Sciences and Technology, 2025)
The study of interaction between ectoparasites and small mammals were conducted at Gunung Ledang Johor National Park, Johor. The objectives of this study were to assess the distribution of small mammals in Gunung Ledang National Park and to identify the ectoparasites found on small mammals in Gunung Ledang National Park. Both hosts species and ectoparasites were identified by laboratory examination using 24 cage traps and 2 mist nets during a 12-day sampling period. The baits that were used in this study were cut ripe banana, dried salted fish and mango. In this study, the results showed a total of 31 volant and non- volant small mammals had been captured and a total of 32 ectoparasites had been collected from the infested small mammals. 14 out of 31 small mammals had infested by ectoparasites which represented 13 of volant species and only 1 of the non-volant species. Among 32 ectorasites, there were 5 species had examined represented 4 species from bat flies and 1 species from ticks. Results also showed that the data analysis on both small mammals and ectoparasites, and ecological factors such as habitat type, elevation and microclimate affect ectoparasite diversity and prevalence. This study effectively assessed the distribution of small mammals in Gunung Ledang, finging ectoparasites linked to these small mammals at both Taman Lagenda and Waterfall Gunung Ledang. This has showed the biological richness of these sites with a notable variety of small mammal species and their ectoparasites. Ectoparasite prevalence and abundance among host species provided important information about host-parasite interactions, highlighting the role of the host behaviour.